1970
DOI: 10.1051/rphysap:019700050101300
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting magnetometers

Abstract: 2014 Under the proper circumstances a current carrying superconductor can generate voltage. This voltage is produced by supercurrent oscillations at frequency 03C9 = 2e/0127 V 2014 a phenomena similar to the Josephson effect in superconducting tunnel junctions. Various structures have been fabricated in which this quantum relation dominates the electrical behavior. These thin film structures have been developed into reliable sensor elements which have been incorporated into various electronic instruments 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…This response is indicative primarily of AM and again is what was anticipated in (8a) when the principal effect of the superconducting ring is as a parametric resistance. The R F drive levels required for maximum response in these two situations also differed by approximately the ratio of 10: 1, (wL/R(wide) : l), as expected from (8). By driving the tank circuit from a constant current source this variation in impedance shows up as a signal voltage which is often used as the basis for magnetometer circuits.…”
Section: )mentioning
confidence: 84%
See 2 more Smart Citations
“…This response is indicative primarily of AM and again is what was anticipated in (8a) when the principal effect of the superconducting ring is as a parametric resistance. The R F drive levels required for maximum response in these two situations also differed by approximately the ratio of 10: 1, (wL/R(wide) : l), as expected from (8). By driving the tank circuit from a constant current source this variation in impedance shows up as a signal voltage which is often used as the basis for magnetometer circuits.…”
Section: )mentioning
confidence: 84%
“…This limit has been analyzed previously [8] and it was found that this situation produces a signal with large harmonic content whose amplitude at the drive frequency (w) is Fig. 2.…”
Section: R and Or If R<mentioning
confidence: 85%
See 1 more Smart Citation
“…as the working temperature T is lowered and becomes ( 5) We may summarize these results as follows. Suppose that we start with a low value of R, so that L >> LG' and that the voltmeter is ideal.…”
Section: Ucrl-20360mentioning
confidence: 89%
“…During the past two years, the energy sensitivity of dc SQUIDs (Superconducting QUantum Interference Devices) [1] has improved by mor~ than 3 orders of magnitude, whi le that of rf SQUIDs [2,3] has improved by perhaps an order of magnitude. The purpose of this article is to review briefly these ~ advances, and to make some assessment of possible future trends.…”
Section: T Introductionmentioning
confidence: 99%